Retaining Repatriate Knowledge at the Crossroads Between Global Knowledge Management and Global Talent Management - Davoine, Eric; Barmeyer, Christoph; Rossi, Clelia (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
While recent contributions introduce the need for dialog between global knowledge management (GKM) and global talent management (GTM) to facilitate repatriate knowledge transfer, a literature gap exists regarding the implementation of this hybrid approach. Using the theoretical backgrounds of repatriate knowledge, GKM and GTM, we define the challenges of retaining repatriate knowledge and suggest approaches to overcome these. Building on the qualitative case study of a German multinational company we introduce a specific organizational measure, the country expert program, which, by being at the crossroads between GKM and GTM and thus facilitating learning, overcomes repatriate knowledge transfer’s major challenges.